Effects of ammonium carbonate post treatment on phenolic resin treated sesenduk (Endospermum diadenum) wood - Ashaari, Zaidon; Lee, Seng Hua; Radzali, Mohd Nor Effendi (Penerbit Universiti Kebangsaan Malaysia, 2015)
The bulking treatment with phenolic resin is well known as a treatment to improve the properties of low density wood but high amount of formaldehyde emission will be released during and after treatment. A study was conducted to determine the performance of phenolic resin treated sesenduk (Endospermum diadenum) wood post treated with ammonium carbonate and urea. Wood strips were treated separately with 30% low molecular weight phenol formaldehyde resin (LmwPF) resin and mixture of LmwPF with urea (30% based on solid PF) using empty-cell process. Two products were produced from the treatment, i.e. impreg and compreg. After conditioning, the surfaces of the samples were applied with ammonium carbonate solution at 10, 20 and 30 g/m2. The samples were then stacked and stored at 60°C for 48 h. Properties such as formaldehyde emission, strength and dimensional stability were evaluated. The results showed that the post treatment with ammonium carbonate has successfully reduced the formaldehyde emission from the sesenduk wood. The degree of reduction was depended on the amount of ammonium carbonate applied on the samples. The results also showed that the sesenduk wood treated with mixture of PF and urea had lower formaldehyde emission. Post treatment with ammonium carbonate did not significantly affect the physical and mechanical properties of the sesenduk wood.